STRATEGI ADAPTASI PEMASARAN KERAJINAN TENUN ULOS PADA PASAR TRADISIONAL, MODERN DAN ON LINE DI TAPANULI UTARA (Studi di Kota Tarutung) - Harisan Boni Firmando (Universitas Islam Negeri Sumatera Utara, 2020)
The writing of journal entitled “Strategy of Marketing Adaptation for Ulos (woven cloth) at Tradisional, Modern and On Line Market in North Tapanuli (Study in Tarutung City)” was begin on the increasing of the number of Ulos merchant at traditional, modern and on line market in North Tapanuli. Merchant the advanced age had change the competition map by build a new marketing strategy. By the entering of the new competitors in the business encourage the entrepreneurs or merchant to have optimal thinking to achieve goal namely to seek and maintain the existence of the customer who has an important rule in the survive of market circulation. The approach method applied in this research is descriptive method by qualitative approach. The data was collected by observation and interview. The analysis unit and information in this research is the merchant and customer of ulos at Tarutung City. The data is interpreted by using the field record. The results of research indicates that the higher of market competition in the area, either in Tarutung or out of Tarutung encourage the merchant of ulos assure the customer through creativity or product innovation.